2016
DOI: 10.5812/jjm.29314
|View full text |Cite
|
Sign up to set email alerts
|

Primer Evaluation for PCR and its Application for Detection of Carbapenemases in Enterobacteriaceae

Abstract: Background:During the last decade, the prevalence of carbapenem-resistant Enterobacteriaceae in human patients has increased. Carbapenemase-producing bacteria are usually multidrug resistant. Therefore, early recognition of carbapenemase producers is critical to prevent their spread.Objectives:The objective of this study was to develop the primers for single and/or multiplex PCR amplification assays for simultaneous identification of class A, class B, and class D carbapenem hydrolyzing β-lactamases in Enteroba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…Mlynarcik et al developed a new set of primers for simultaneously detection of 11 genes including bla KPC , bla OXA , bla VIM , bla NDM , bla IMP , bla SME , bla IMI , bla GES , bla GIM , bla DIM and bla CMY . The results of that study revealed their technique was a reliable method for screening of all mentioned carbapenemase genes in Enterobacteriaceae (27).…”
Section: Discussionmentioning
confidence: 95%
“…Mlynarcik et al developed a new set of primers for simultaneously detection of 11 genes including bla KPC , bla OXA , bla VIM , bla NDM , bla IMP , bla SME , bla IMI , bla GES , bla GIM , bla DIM and bla CMY . The results of that study revealed their technique was a reliable method for screening of all mentioned carbapenemase genes in Enterobacteriaceae (27).…”
Section: Discussionmentioning
confidence: 95%
“…A literature review was carried out to determine the potential of resistance by molecular methodology found in this study, which has genes described in the literature that encode the β-lactamase enzyme. The result of the literary survey is shown in Table 3 [ 3 , 6 , 16 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ...…”
Section: Discussionmentioning
confidence: 99%
“…Identification of genes encoding for carbapenemases on mobile genetic elements emerged the possible horizontal spread of these enzymes. 4,11,12 There are various phenotypic methods for identifying β-lactamases enzyme-producing of P. aeruginosa, each with disadvantages and benefits. 3 Double-disk synergy test for detection of strains belongs to class A β-lactamases, Modified Hodge test to detect class A β-lactamases and meropenem E-test strip to identify class B β-lactamases is common tests.…”
Section: Introductionmentioning
confidence: 99%